2022
DOI: 10.1108/apjml-10-2021-0777
|View full text |Cite
|
Sign up to set email alerts
|

What motivates consumers to be in line with online shopping?: a systematic literature review and discussion of future research perspectives

Abstract: PurposeThis study conducts a systematic literature review to synthesize the extant literature primarily on “online shopping consumer behavior” and to gain insight into “What drives consumers toward online shopping”.Design/methodology/approachThe authors followed guidelines for systematic literature reviews with stringent inclusion and exclusion criteria. The review is based on 79 research papers published from 2000 to 2020 in 21 reputed peer-reviewed international journals. The papers were analyzed and synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 117 publications
0
19
0
3
Order By: Relevance
“…During the COVID-19 people preferred to shop online because it helped them save time and protect from the disease (Fudzi et al, 2021;Mehrolia et al, 2021). Consumers' perception of the benefits associated with OS is characterized as convenience, product comparison (Bhatti & Rehman, 2019), product selection, ease and comfort, pricing, enjoyment, speed of service, and security of making transactions (Bhojanna & Archana, 2020;Srivastava & Thaichon, 2023). Hypothesis H2.…”
Section: Pb At and Bitosmentioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 people preferred to shop online because it helped them save time and protect from the disease (Fudzi et al, 2021;Mehrolia et al, 2021). Consumers' perception of the benefits associated with OS is characterized as convenience, product comparison (Bhatti & Rehman, 2019), product selection, ease and comfort, pricing, enjoyment, speed of service, and security of making transactions (Bhojanna & Archana, 2020;Srivastava & Thaichon, 2023). Hypothesis H2.…”
Section: Pb At and Bitosmentioning
confidence: 99%
“…During the COVID‐19 people preferred to shop online because it helped them save time and protect from the disease (Fudzi et al, 2021; Mehrolia et al, 2021). Consumers' perception of the benefits associated with OS is characterized as convenience, product comparison (Bhatti & Rehman, 2019), product selection, ease and comfort, pricing, enjoyment, speed of service, and security of making transactions (Bhojanna & Archana, 2020; Srivastava & Thaichon, 2023). Consumers' PB to buy online enhances when the website is user‐friendly, information about products and services can be traced effortlessly, with minimal page load time and an easy and safe ordering process (Al‐Debei et al, 2015; Giao & Tuan, 2021).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Furthermore, previous studies have identified website design, website security, and customer service are among the factors that help to improve online customer experience and satisfaction, which will then lead to the customer deciding to purchase via an online shopping platform (Srivastava & Thaichon, 2022;Deyalage & Kulathunga, 2019;and Dang & Pham;. According to Daroch et al (2021) and Yang et al (2019), to compete in the e-commerce market, a company should understand the type of customers by differentiating the way they treat them based on the level of online customer experience.…”
Section: Online Customer Experiencementioning
confidence: 99%
“…The electronic payment site functionality, such as privacy, security, speed of service, and customer information, are the factors that lead to customer satisfaction and loyalty for the success of online shopping platforms (Ehsani & Hosseini, 2021;Sanyala & Hisamb, 2019;Tandon et al, 2017). Trustworthy website security features such as general company information as well as the privacy and security policies during online purchase transactions should be provided and well-designed to promote a higher sense of low risks and reduce customer safety concerns (Kim, 2019;Sánchez-Torres et al, 2018;Srivastava & Thaichon, 2022).…”
Section: Website Securitymentioning
confidence: 99%
“…Third, prior reviews have focused on the digitalization of brands' business models (Favoretto et al, 2022), predominantly from a large-brands perspective. Fourth, consumers' perceived value motivations for online shopping have been addressed (Srivastava & Thaichon, 2023) but not specifically in relation to the DTC retail model.…”
Section: Introductionmentioning
confidence: 99%